2022
DOI: 10.1021/acs.iecr.2c01847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tacticity and Degree of Sulfonation of Polystyrene Sulfonate on Calcium-Binding Behavior in the Presence of Dodecyl Sulfate

Abstract: The hardness-causing ions like calcium are detrimental to the performance of anionic surfactants like dodecyl sulfate. Polystyrene sulfonate is an essential component of ion exchange resins that are used to adsorb such ions. Therefore, understanding the binding behavior of calcium ions to polystyrene sulfonate in the presence of dodecyl sulfate is of industrial relevance. Two important structural parameters of polystyrene sulfonate are known to influence its behavior: (i) The arrangement of aromatic groups aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…In the case of PSS, the proportion of hydrophobic regions and charge separation can be varied by changing the degree of sulfonation. In our previous study, we observed that lowering the degree of sulfonation increased the PSS-DS association due to greater hydrophobic attraction and the formation of calcium ion bridges between sulfonate and sulfate groups . The effect of cross-linking on such an association remains to be studied.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In the case of PSS, the proportion of hydrophobic regions and charge separation can be varied by changing the degree of sulfonation. In our previous study, we observed that lowering the degree of sulfonation increased the PSS-DS association due to greater hydrophobic attraction and the formation of calcium ion bridges between sulfonate and sulfate groups . The effect of cross-linking on such an association remains to be studied.…”
Section: Introductionmentioning
confidence: 92%
“…The interaction between like-charged polyelectrolytes and surfactants , has received lesser attention than that between oppositely charged or neutral polyelectrolytes and surfactants. In our previous work, we discussed the possibility of achieving the desired response of PSS-Ca binding to the presence of the anionic surfactant dodecyl sulfate (DS). Additionally, we also investigated the effect of tacticity and the degree of sulfonation on the above response . Both simulation studies considered free PSS chains.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations